Hurricane Toads - Steve A Johnson; Candace D Furhmann (EDIS)
Eastern spadefoots are a common but largely unappreciated species of native toad in Florida. Following torrential rains they emerge from hiding and breed in shallow pools. In as little as 14 days, hordes of raisin-sized froglets emerge and hop away in all directions from the pond or puddle where they were born. Some of them find their way to yards and garages of suburban neighborhood homes. Other unlucky baby toads end up on roads, where they are smashed. This 5-page fact sheet written by Steve A. Johnson and Candace D. Fuhrmann and published by the UF/IFAS Department of Wildlife Ecology and Conservation outlines the unique biology of this species and explains how to identify eastern spadefoot tadpoles, young, and adults. It also includes a section on how you and your friends and family can help these interesting and attractive little creatures by engaging in citizen science. https://edis.ifas.ufl.edu/uw474